Islamic Boarding School Counseling in Handling New Students Experiencing Maladjustment - Anisah Prafitralia; Suryadi Suryadi; Mursalim Mursalim; Wike Silfia; Nasirudin Al Ahsani (Scidacplus, 2026)
This research is motivated by the phenomenon of maladjustment among new students at the Nurul Jadid Islamic Boarding School in Probolinggo, specifically their difficulties adjusting to the environment, rules, and patterns of life at the boarding school. This problem results in low motivation, stress, and even rule-breaking behavior. The purpose of this study is to determine the role of the boarding school administrators in reducing maladjustment among new students, identify the forms of maladjustment that arise, and describe the Islamic counseling program implemented at the boarding school. The research method used a descriptive qualitative approach with a post-positivist paradigm. Data were collected through observation, documentation, and structured interviews with administrators, students, and their families. The results indicate that maladjustment among new students manifests as a lack of discipline, homesickness, difficulty establishing social relationships, and rule violations. The boarding school administrators play a crucial role in fostering discipline, providing religious guidance, and providing counseling services based on Islamic values. The counseling program includes the administrators' role in maintaining justice and equality in the application of sanctions for disciplinary violations.